Bat-borne polyomaviruses in Europe reveal an evolutionary history of intrahost divergence with horseshoe bats distributed across the African and Eurasian continents. (9th October 2020) - Vidovszky, Márton Z.; Tan, Zhizhou; Carr, Michael J.; Boldogh, Sándor; Harrach, Balázs; Gonzalez, Gabriel
Abstract : Polyomaviruses (PyVs) are small, circular dsDNA viruses carried by diverse vertebrates, including bats. Although previous studies have reported several horseshoe bat PyVs collected in Zambia and China, it is still unclear how PyVs evolved in this group of widely dispersed mammals. Horseshoe bats (genus Rhinolophus ) are distributed across the Old World and are natural reservoirs of numerous pathogenic viruses. Herein, non-invasive bat samples from European horseshoe bat species were collected in Hungary for PyV identification and novel PyVs with complete genomes were successfully recovered from two different European horseshoe bat species. Genomic and phylogenetic analysis of the Hungarian horseshoe bat PyVs supported their classification into the genera Alphapolyomavirus and Betapolyomavirus . Notably, despite the significant geographical distances between the corresponding sampling locations, Hungarian PyVs exhibited high genetic relatedness with previously described Zambian and Chinese horseshoe bat PyVs, and phylogenetically clustered with these viruses in each PyV genus. Correlation and virus–host relationship analysis suggested that these PyVs co-diverged with their European, African and Asian horseshoe bat hosts distributed on different continents during their evolutionary history. Additionally, assessment of selective pressures over the major capsid protein (VP1) of horseshoe bat PyVs showed sites under positive selection located in motifs exposed to the exterior of the capsid. In summary, our findings revealed a pattern of stable intrahost divergence of horseshoe bat PyVs with their mammalian hosts on the African and Eurasian continents over evolutionary time.